Proposal of a methodology to quantify the antibacterial activity of honey. (FAVE Sección Ciencias Veterinarias, 2021)
In this study a standardized method for objectively comparing the antibacterial activity of honey was developed. The assay was performed using a strain of S. aureus and four honeys that have been shown antibacterial activity against this strain. The antibacterial activity of honeys were checked by using an agar plate diffusion method using S. aureus (ATCC 29213) as the test organism. On the surface of each agar plate six stainless steel cylinders with a diameter of 8,14 mm were radially disposed. Onto each cylinder 0,1 mL of sample honey at 10% v/v was placed and all Petri dishes were incubated at 35°C during 24 h. Each sample were analyzed by triplicate. The surface of the cylinder diameter was set as reference antibacterial activity equivalent to minimal inhibitory concentration (MIC). The antibacterial activity of each honey was quantitated by the relationship between the surface of the inhibitory zone and the surface of the reference activity expressed as multiples of MIC (x MIC). The method allowed establishing differences between the bacterial activities of the different honeys tested and could be used for identifying honeys that could be employed with medicinal purpose for the treatments of wounds.
Keywords: Honey, Staphylococcus aureus, Quantitation, Antibacterial activity.